Benefits of Zebrafish Xenograft Models in Cancer Research - Xingyu Chen; Xingyu Chen; Yongyun Li; Yongyun Li; Tengteng Yao; Tengteng Yao; Renbing Jia; Renbing Jia (Frontiers in Cell and Developmental Biology, 2021)
As a promising in vivo tool for cancer research, zebrafish have been widely applied in various tumor studies. The zebrafish xenograft model is a low-cost, high-throughput tool for cancer research that can be established quickly and requires only a small sample size, which makes it favorite among researchers. Zebrafish patient-derived xenograft (zPDX) models provide promising evidence for short-term clinical treatment. In this review, we discuss the characteristics and advantages of zebrafish, such as their transparent and translucent features, the use of vascular fluorescence imaging, the establishment of metastatic and intracranial orthotopic models, individual pharmacokinetics measurements, and tumor microenvironment. Furthermore, we introduce how these characteristics and advantages are applied other in tumor studies. Finally, we discuss the future direction of the use of zebrafish in tumor studies and provide new ideas for the application of it.